Financial development and industrial capital accumulation - Bossone, Biagio (Policy research working paper, 1999)
There may be a compelling discontinuity to financial sector development in that banks need to be supported early in development but need to be "weakened" later, at the expense of bank rents, to foster further development. The important question for policy is when and how to generate and manage this discontinuity so that it is not forced on society by costly and traumatic events such as bank failures